Penerapan Strategi Pembelajaran Kooperatif Model (STAD) Dalam Pembelajaran Maharah Kitabah Menggunakan Strip Story Di MTs Sa Al-Hidayah - Jumiat; Maksum, M. Syukron; Aminudin; Mastur, Al Akcbar (STAIN MAJENE, 2025)
This study aims to describe the implementation of the Student Teams Achievement Division (STAD) strategy combined with Strip Story media in learning maharah al-kitabah and analyze its influence on student activity, collaboration, and writing skills. The study used a descriptive qualitative approach, with subjects of grade VIII MTs SA Al-Hidayah. Data were collected through observation, interviews, and documentation, then analyzed using the Miles & Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The results showed that the integration of STAD with Strip Story media was able to create collaborative and communicative learning. The average group score was in the good category (72–76), with a student collaboration level reaching 87% and activity level of 80%. Strip Story media plays a role in helping students develop storylines, enrich vocabulary, and express ideas in writing. Thus, this strategy not only improves Arabic writing skills but also forms responsibility and learning motivation through teamwork. This finding is an innovative alternative in Arabic language learning that is oriented towards processes and results.